Prevalence of Silent Myocardial Ischemia in patients with Type 2 Diabetes Mellitus attending Medical Outpatient Clinics - Samiullah Khan, Sadullah Shah, Naimat Ullah Shah, Saeed Maqsood, Radhia Khan, Muhammad Saad Jibran (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Silent myocardial ischemia (SMI) is a disease that is well-known and yet frequently misdiagnosed as a cardiovascular complication of type 2 diabetes mellitus (T2DM). Ischemic symptoms can be hidden by autonomic neuropathy and distorted pain perception, coronary artery disease may develop without notice. Risk stratification and prevention of adverse cardiac events Risk stratification and prevention of adverse cardiac events are important in early identification of SMI. Objective: To ascertain the occurrence of silent myocardial ischemia and its risk factors in patients with type 2 diabetes mellitus who visited medical outpatient clinics. Methods: It was a cross-sectional study at the Medical Teaching Institution Bannu and Medical Teaching institution DI Khan during six months between November 2022 and April 2023. The patients that were enrolled were adult patients who had known T2DM and had no angina or any history of coronary artery disease. Demographic information, diabetes history and cardiovascular risk factors were taken. Each of the subjects was subjected to 12-lead electrocardiography at rest after which exercise stress testing or ambulatory ECG surveillance against individual indications to identify silent ischemia. Data analysis was done with the help of relevant statistical tests and significance level was taken to be p<0.05. Results: Silent myocardial ischemia had been found in 32 percent of the patients. Older age groups, longer duration of diabetes and coexisting hypertension and dyslipidemia were found to have higher prevalence. Resting ECG made the observation that a large percentage of cases were well diagnosed whereas stress testing enhanced the diagnostic accuracy among patients whose initial ECG showed normalcy. Conclusion: Patients with type 2 diabetes mellitus have silent myocardial ischemia. Early intervention and minimization of cardiovascular morbidity in the future may be achieved by regular screening, especially among high-risk populations. Keywords: Mute myocardial ischemia; Type 2 diabetes mellitus; Electrocardiography; Cardiovascular risk factors.